2020
DOI: 10.1155/2020/8876230
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition of Neonatal Maternal Separation to Visceral Hypersensitivity via Downregulation of Small-Conductance Calcium-Activated Potassium Channel Subtype 2 (SK2) in Mice

Abstract: Background. Visceral hypersensitivity is a common occurrence of gastrointestinal diseases such as irritable bowel syndrome (IBS), wherein early-life stress (ELS) may have a high predisposition to the development of visceral hypersensitivity in adulthood, with the specific underlying mechanism still elusive. Herein, we assessed the potential effect of small-conductance calcium-activated potassium channel subtype 2 (SK2) in the spinal dorsal horn (DH) on the pathogenesis of visceral hypersensitivity induced by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Sucrose preference test (SPT) was performed as we previously reported (Wu et al, 2020). Briefly, mice were individually housed to habituate drinking water with two bottles fitted with ballpoint sippers for 2 days.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…Sucrose preference test (SPT) was performed as we previously reported (Wu et al, 2020). Briefly, mice were individually housed to habituate drinking water with two bottles fitted with ballpoint sippers for 2 days.…”
Section: Sucrose Preference Testmentioning
confidence: 99%
“…Early life is the critical window for the development of gut microbiota, gut and brain ( Laursen et al, 2021 ; Ratsika et al, 2021 ). Therefore, disturbance of this process, such as caused by ELS, may have a high predisposition to the development of IBS in adulthood ( Wu et al, 2020 ). We found that MS affected the composition of both ileal and fecal microbiota ( Figures 6 , 7 ), suggesting MS affected intestinal microbiota community from early life to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal separation (MS) is a classic animal model of IBS, which effectively mimics ELS ( Riba et al, 2018 ; Wong et al, 2019 ; Huang S. T. et al, 2021 ; Tao et al, 2022a ). Using MS model, some of the pathogeneses of IBS were widely studied, such as visceral hypersensitivity ( Wu et al, 2020 ; Huang S. T. et al, 2021 ; Wang et al, 2022 ; Tao et al, 2022a ), intestinal hyperpermeability ( Kuti et al, 2020 ; Torres-Maravilla et al, 2022 ), intestinal dysmotility ( Bülbül and Sinen, 2021 ), intestinal dysbiosis ( Rincel and Darnaudéry, 2020 ; Park et al, 2021 ), and anxiety-like and depressive-like behaviors ( Zhou et al, 2022 ; Favoretto et al, 2023 ). Also, Riba et al ( Riba et al, 2018 ) systematically studied the influence of MS on the function of the intestine, mimicking IBS’s main features, including intestinal hyperpermeability, visceral hypersensitivity, microbiota dysbiosis, bile acid malabsorption, and low grade inflammation in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of SK2 channels increases neuronal excitability and enhances excitatory synaptic transmission, as indicated by an increased frequency of miniature excitatory postsynaptic currents and action potentials, leading to hyperexcitability and pain hypersensitivity 169 . Recent research has shown that visceral hypersensitivity is related to the downregulation of SK2 channel proteins as well as the inactivation of SK2 channels in PVN CRH neurons 15 , 170 , 171 . Injecting SK2 channel activators into the PVN can reverse visceral hypersensitivity.…”
Section: Pvnmentioning
confidence: 99%